2019
DOI: 10.1111/jan.14129
|View full text |Cite
|
Sign up to set email alerts
|

The experience of hope in families of children and adolescents living with chronic illness: A thematic synthesis of qualitative studies

Abstract: Aim To synthesize qualitative studies on the experience of hope in families of children and adolescents living with chronic illness. Background Hope is multidimensional, dynamic, and varies according to experienced events, cultural environments and stage of life. The qualitative synthesis of the experience of hope in the paediatric population with chronic conditions is scarce. Design Thematic synthesis of qualitative studies. Data sources A systematic literature search in PubMed, CINAHL, LILACS, PsycINFO, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…Prior conceptualizations of hope narrowly defined it in relation to therapeutic goals and future aspirations, and emphasized intrapersonal characteristics [ 17 ]. A thematic analysis of qualitative studies addressing the experience of hope among children with chronic illness by Leite et al identified five themes: uncertainty, support, information, between “dark thoughts” and positive thoughts, and hoping to go back to normality [ 11 ]. The attributes of hope identified in our study ( Figure 1 ) included internal states of vitality and energy, future focus, as well as characterization of personal identity and one’s value and potential for impact on the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior conceptualizations of hope narrowly defined it in relation to therapeutic goals and future aspirations, and emphasized intrapersonal characteristics [ 17 ]. A thematic analysis of qualitative studies addressing the experience of hope among children with chronic illness by Leite et al identified five themes: uncertainty, support, information, between “dark thoughts” and positive thoughts, and hoping to go back to normality [ 11 ]. The attributes of hope identified in our study ( Figure 1 ) included internal states of vitality and energy, future focus, as well as characterization of personal identity and one’s value and potential for impact on the world.…”
Section: Discussionmentioning
confidence: 99%
“…Less well studied are the promoting and inhibiting factors that influence hope. Few studies have examined hope in the context of pediatric chronic illness [ 8 , 9 , 10 , 11 ]. Therefore, we determined that further formative work was needed in partnership with patients and caregivers to develop a conceptual model to guide our research.…”
Section: Introductionmentioning
confidence: 99%
“…The reestablishment of the meaning and purpose of life is related to the acceptance of the chronic condition and the beliefs that integrate with the purpose of life (Clayton-Jones et al, 2016). For this reason, children and adolescents seek to find the existence of a reason for this experience and that the future may still be promising (Leite, García-Vivar, Neris, Alvarenga, & Nascimento, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hope for normalcy, positive expectations regarding treatment, optimism, courage and confidence to live life and achieve dreams characterized this need. The fear of the future impacting on hope was also highlighted in a literature review on the hope of families of children with chronic illnesses (Leite, García-Vivar, Neris, Alvarenga, & Nascimento, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation